RESPON PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonicum L. Var. TUKTUK) ASAL BIJI TERHADAP PEMBERIAN PUPUK KALIUM DAN JARAK TANAM - Benhard H. Sitepu; Sabar Ginting; Mariati Mariati (Jurnal Agroekoteknologi, 2013)
The aim of the research was to evaluated the effect of potassium fertilizer (K) andthe planting distance on the growth and yield of onion (Allium ascalonicum L.)varieties Tuktuk. The research used Randomized Block Design with two-factors.The first factor was the doses of potasium fertilizer (KCl) with four levels e.g : K0= without KCl (control), K1=10 g KCl/m², K2= 20 g KCl/m² and K3 = 30 gKCl/m². The second factor was planting distance with three levels e.g : J1 = 10x10cm, J2 = 10 x 15 cm and J3 = 10 x 20 cm. The results showed that the diameterof tubers, wet weight of tubers per sample and dry weight of tubers per samplewere significantly affected by potasium fertilizers. The higest of diameter oftubers, wet weight of tubers per sample and dry weight of tubers per sample wereproduced by K2, whistling of each were 3,72 cm, 18,69 g and 5,61 g, but plantheight and leafs number were unsignificantly. Where as, plant height weresignifcantly affacted by planting distance were prouced by J2 e.g 16,01 cm, butleafs of number, diameter of tubers, wet weight of tubers per sample and dryweight of tubers per sample unsignificantly. Interaction of potasiumfertilizer and planting distance significantly affected the wet weight oftubers per plot and dry weight of tubers per plot. The higest of wetweight of tubers per plot and dry weight of tubers per plot wereproduce by K2J1 were 1,34 kg and 0,40 kg.__________________________________________________________________Key words: onion, potassium fertilizer and planting distance